Fertilizantes organominerais e bioestimulantes na soja - Oliveira, Lírian França (2023)
Soybeans are of great economic importance both nationally and worldwide. Therefore, there is a need to look for new sources of nutrients or growth promoters to help the crop develop, such as biostimulants and organomineral fertilizers, in order to achieve high yields. The objective of this work was to evaluate growth and yield attributes in response to the use of biostimulants and organomineral fertilizers in soybean cultivation. Two experiments were conducted, one in the municipality of Uberlândia-MG and the other in Pedrinópolis-MG, in the 2021/2022 harvest, in a randomized block design, with four replications. In the Uberlândia experiment, 8 treatments were used: T1- organomineral fertilizer at sowing; T2 to T5- organomineral fertilizer at sowing and foliar application of the biostimulant , at doses of 0.5; 1; 2 and 4 L ha-1, spread over the V4 and R1 stages; T6-organomineral fertilizer together with the application of the biostimulant at a dose of 2.0 L ha-1 in the planting furrow; T7- no application (negative control); T8- mineral fertilization (positive control). In the other experiment, 10 treatments were used, in which T1 to T4- biostimulant 1 foliar , in 4 doses (0.5; 1; 2 and 4 L ha-1) divided into stages V4 and R1; T5 and T6- biostimulant 1 (2 ml kg seed-1 and 10 ml kg seed-1, respectively); T7- bioregulant (0.5 L ha-1) foliarapplication in installments at stages V4 and R1; T8- biostimulant 2 (2 ml kg seed-1); T9-biostimulant 3 (2 ml kg seed-1); and T10- no biostimulant. In this experiment, 250 kg ha-1 of the mineral fertilizer formulation 7-35-10 was applied to all treatments. In the first experiment, it was found that the use of organomineral fertilizer with or without biostimulant gave better results in terms of growth productivity and parameters. Nor did they differ from mineral fertilization. The method of application of the biostimulant influenced soybean yields, but the different doses did not lead to differences in the parameters evaluated. In the second experiment, it was observed that the use of biostimulants 1, 2, 3, bioregulators and control (no application) in the soybean crop did not provide significant differences for the growth and productivity variables. Biostimulant 1 in all doses foliar application at stages V4 and R1 of the soybean or seed treatment did not provide significant increases for the characters evaluated. Biostimulants 2 and 3 at a dose of 2 ml kg seed-1 and the bioregulator at a dose of 0.5 L ha-¹ applied foliar did not prove to be superior to the treatment without application of biostimulant and bioregulator.